REPRESENTASI PENERIMAAN DIRI PADA TOKOH SPEKTRUM AUTISME DALAM DRAMA KOREA EXTRAORDINARY ATTORNEY WOO - Auliya, Nurul (Journal Communication Specialist, 2025)
Self-acceptance is very important for everyday life. This self-acceptance can be seen in a Korean drama entitled Extraordinary Attorney Woo which discusses lawyers with autism spectrum disorders. Researchers are interested in analyzing how self-acceptance is represented in the Korean drama Extraordinary Attorney Woo. This study uses a qualitative method with semiotic analysis from John Fiske which divides social codes into reality levels, representation levels, and ideology. The materials for this research are 8 scenes in the Korean drama Extraordinary Attorney Woo episodes 1, 3 and 4 which visualize representations of self-acceptance. The results of this study are that there are several stages of self-acceptance in the Korean drama Extraordinary Attorney Woo, namely the rejection stage, the depression stage, the diversion stage, and the acceptance stage. This drama also shows that families with children with autism need social support for their mental health.